Effects of cutting parameters on temperature and temperature prediction in micro-milling of Inconel 718. (2018) - Lu, Xiaohong; Wang, Hua; Jia, Zhenyuan; Feng, Yixuan; Liang, Steven Y.
Inconel 718 is a kind of typical difficult-to-machine material. Micro-milling technology is an effective method for fabricating micro parts of Inconel 718. The change rules of micro-milling temperature differ from those of the traditional processing, which will affect the surface integrity of the workpiece and the tool life of the micro-milling cutter in different ways. To ascertain the effects of cutting parameters on cutting temperature during micro-milling Inconel 718 and achieve the prediction of cutting temperature, some micro-milling experiments are conducted based on the response surface method. The independent and interaction effects of the spindle speed, feed per tooth and axial cutting depth on cutting temperature are investigated. A micro-milling temperature prediction model is established based on the experiment results. The maximum prediction error is 5.3% and the average prediction error is 2.6%. Finally, the accuracy of the proposed model is validated through experiments of micro-milling Inconel 718.